Characteristics of Black Soldier Fly Maggot Snack Bar and The Potential as Stunting Prevention Food - Made Dita Dewi DEVANI; I Gede Arie Mahendra PUTRA; I Gusti Agung Bulan Mutiara DEWI; Ida Ayu Tisna WAHYUNIARI (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology)
Stunting remains unresolved, often due to protein deficiency. Black Soldier Fly larvae flour, with 57.86% protein, can address this as a high-protein snack bar ingredient. Cultivating larvae on vegetable and fruit waste also reduces food waste. This study aimed to determine the effects of BSFL Flour substitution on snack bars’ physical, chemical, and sensory characteristics and to find the optimal substitution level for the best results. This study used a simple Randomized Group Design (RGD) to compare wheat flour to BSFL Flour (100:0, 95:5, 90:10, 85:15, and 80:20), with treatments repeated 3 times to get 15 experimental units. The data obtained were analyzed by variance and ’continued with Tukey’s test if it was significant. The results showed ratio of wheat flour to BSFL Flour (95:5) produced snack bar with the best characteristics with a hedonic average value for color 4.44 (slightly liked), aroma 4.06 (slightly liked), texture 4.00 (slightly liked) taste 4.13 (slightly liked), and overall acceptances 4.06 (slightly liked), with a protein content of 8.12%, ash content 1.75%, hardness 96.39 N and color characteristics L* 32.06, a* 5.56, and b* 24.46 with Irish Coffee color criteria. The development of a snack bar with BSFL Flour also has the potential as a stunting prevention food.